LC–HRMS for the identification of quercetin and its derivatives in Spiraea hypericifolia (Rosaceae) and anatomical features of its leaves - Petrova, Natalia V.; Chernonosov, Alexander A.; Koval, Vladimir V.; Andreeva, Valeria Yu; Erst, Andrey S.; Kuznetsov, Alexander A.; Kulikovskiy, Maxim S.; Wang, Wei; Yu, Sheng-Xiang; Kostikova, Vera A. (Plants)
Spiraea hypericifolia L. is affiliated with the section Chamaedryon Ser. of the genus Spiraea L. (Rosaceae). Similar to many other Spiraea species, S. hypericifolia most often accumulates flavonols among other flavonoids, in particular quercetin and its derivatives. An ethanol–water extract from the aerial part of S. hypericifolia collected in the vicinity of the Ilyichovo settlement (Krasnoyarsk Krai, Russia) was analyzed by liquid chromatography with high-resolution mass spectrometry. Primary and secondary metabolites were found in the extract; structural interpretation consistent with quercetin and its derivatives was proposed for 10 of them. Major compounds were various glycosides of quercetin containing glucose (four compounds), galactose (one compound), xylose (two compounds), arabinose (one compound), or rutinose (one compound) as a carbohydrate residue. Isorhamnetin and 3-O-methylquercetin-3′-O-β-D-glucopyranoside were identified among methyl-containing compounds. The latter compound and reynoutrin, rhamnetin-3-O-β-D-xylopyranosyl-β-D-glucopyranoside, and quercetin-3-O-(6″-O-malonyl)-β-D-glucoside have not been previously found in S. hypericifolia. Data on the presence of quercetin and its derivatives in the extract of S. hypericifolia expand the understanding of the possible practical use of this plant. In addition, the microscopic features of S. hypericifolia leaves were studied. The diagnostic features of the leaf blade necessary for the authentication of raw materials were revealed: straight-walled epidermis cells, stomata located on both sides of the leaf blade (amphistomatic type), two types of trichomes, and wrinkled cuticula with nodi. The main anatomical diagnostic features of the leaves of S. hypericifolia were determined, which makes it possible to assess the authenticity of the raw material.